Cultures of Restraint and Towards an Appraisal of Non-Western News Values - Subin, Paul; Sosaleb, Sujatha (Taylor & Francis, 2023)
Research on Western European and North American news media continues to dominate scholarship in the field of journalism studies. The remedies sought to rectify this imbalance notably include comparative studies across non-Western and Western countries using large-scale surveys or content analyses. At an epistemological level, such studies adopt—often inherently—an Enlightenment-inspired normative frame that makes the comparisons and transpositions possible. On the one hand, these normative frames are necessary placeholders to make sense of the global field of journalism considering existing hierarchies of knowledge production. On the other, such frames are untenable because they conveniently force Enlightenment-based assumptions upon non-Western cultures, which fundamentally exist in tension with those normative assumptions. Departing from such comparative studies and approaches, this article proposes the concept of “cultures of restraint” to understand non-Western journalism practices and news values in a more context-sensitive manner. We demonstrate the utility of this concept by applying it to the case of vernacular language migrant journalists in the Middle East. Drawing on fieldwork and interviews, we illuminate the cultural conditions that shape the journalistic task of redefining “normative” news values, in the process challenging conventional interpretations of news and journalism.
Keywords: 59 Ciencia Política::5910 Opinión pública ::5910.02 Medios de comunicación de masas; ODS 10 - Reducción de las desigualdades; Non-Western news values; Global South; De-westernizing media studies; vernacular news cultures; cultures of restraint; postcolonial communication